2020
DOI: 10.3390/ijerph17165928
|View full text |Cite
|
Sign up to set email alerts
|

Tendency to Worry and Fear of Mental Health during Italy’s COVID-19 Lockdown

Abstract: Background: We tested whether the tendency to worry could affect psychological responses to quarantine by capitalizing on the opportunity of having collected data before the COVID-19 outbreak on measures of worry, anxiety, and trait mindfulness in a group of university students. Methods: Twenty-five participants completed self-report measures assessing worry (Penn State Worry Questionnaire, PSWQ), anxiety (Anxiety Sensitivity Index, ASI-3), and trait mindfulness (Mindful Attention Awareness Scale, MAAS) at T0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 37 publications
(43 reference statements)
3
90
0
1
Order By: Relevance
“…The positive relationship between anxiety and poor sleep quality has been extensively investigated and was confirmed during lockdown [ 9 , 20 , 26 ]. While the cross-sectional design of our study does not allow us to verify whether the symptoms of psychological distress that we documented were related to the restrictions imposed to curtail the spread of the SARS-CoV-2 virus, a causal relationship is plausible, as also suggested by the literature [ 9 , 10 , 15 , 16 , 20 , 28 ]. The convenience sample investigated was recruited in the Province of Reggio Emilia, one of the most affected Italian provinces during the early phase of the pandemic.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The positive relationship between anxiety and poor sleep quality has been extensively investigated and was confirmed during lockdown [ 9 , 20 , 26 ]. While the cross-sectional design of our study does not allow us to verify whether the symptoms of psychological distress that we documented were related to the restrictions imposed to curtail the spread of the SARS-CoV-2 virus, a causal relationship is plausible, as also suggested by the literature [ 9 , 10 , 15 , 16 , 20 , 28 ]. The convenience sample investigated was recruited in the Province of Reggio Emilia, one of the most affected Italian provinces during the early phase of the pandemic.…”
Section: Discussionmentioning
confidence: 82%
“…These results suggest that lockdown might impact sleep quality and that this association could be mediated by crucial determinants of health, such as physical activity and diet, and to a lesser extent, smoking and alcohol consumption, the presence of financial problems, and symptoms of psychological distress. Indeed, anxiety was widespread among the Italian population during lockdown, as were feelings of uncertainty, fear, and loneliness [ 9 , 10 ]. This impact on sleep quality was seen especially among females, those with low education level, and those who experienced financial problems.…”
Section: Discussionmentioning
confidence: 99%
“…Fear is a powerful emotion that can affect human behavior and job performance. One study on the psychological impact of quarantine in Chinese university students found that 24.9% of those interviewed experienced anxiety related to the COVID-19 outbreak (Baiano et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…All of these are found to be relatively less among those with good knowledge of the pandemic and least among those who are not well-informed about the same. The latter, besides being less aware or less accepting of their thoughts, might be engaging in maladaptive thoughts and actions as well as emotional avoidance, not being able to commit to doing what is valuable to the self (Baiano et al, 2020).…”
Section: Discussionmentioning
confidence: 99%